Centroid Moment Tensor of the 2019 MW 5.7 Changning Earthquake Refined Using 3D Green’s Functions Considering Surface Topography - Huo, Yuanhang; Zhang, Wei; Zhang, Jie (Frontiers in Earth Science, 2021)
The Mw 5.7 Changning earthquake occurred in southern Sichuan basin on 17 June, 2019 and was the largest event ever recorded in this region. There are still some arguments existing about the causes of the earthquake and its possible links with water injections. Many studies on this earthquake have been performed, but the event depths obtained among them are significantly different and the source mechanisms also exhibit variations. In this study, we design an inversion scheme and use 3D Green’s functions considering the rugged topography of this region to determine the event location and moment tensor of the Changning earthquake based on waveform fittings. The 3D model can reduce the uncertainty due to the approximation of 1D model and better constrain the solutions. The latitude and the longitude of event location are 28.34°N and 104.82°E respectively and the depth is 3.14 km. The nodal plane solutions are strike 295°/dip 88°/rake 14° and strike 204°/dip 76°/rake 178°. The percentages of DC, CLVD and ISO components are 10%, -83% and -7%, respectively. The good waveform fittings at 17 broadband stations indicate the reliability of the source mechanism in this study.